The diversity and sustainability of ornamental plants traded by guarani communities of Misiones Province, Argentina - Keller, Hector Alejandro (2010)
The study covers ornamental plants species that are traded by two Guarani communities in Argentina. The trade is described, as well as the frequency, abundance and diversity of plants for sale on roadside stalls, along with the income they generate. Harvested and unharvested areas of forest are compared; the relative impacts of Guarani harvest and commercial timber extraction on ornamental plants are evaluated, and some traditional Guarani beliefs are described that regulate the harvest of ornamental plants by the Guarani.